2007
DOI: 10.1002/dneu.20362
|View full text |Cite
|
Sign up to set email alerts
|

Time course analysis of gene expression during light‐induced photoreceptor cell death and regeneration in albino zebrafish

Abstract: Constant intense light causes apoptosis of rod and cone photoreceptors in adult albino zebrafish. The photoreceptors subsequently regenerate from proliferating inner nuclear layer (INL) progenitor cells that migrate to the outer nuclear layer (ONL) and differentiate into rods and cones. To identify gene expression changes during this photoreceptor regeneration response, a microarray analysis was performed at five time points during the light treatment. The time course included an early time point during photor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
296
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 195 publications
(334 citation statements)
references
References 62 publications
21
296
1
1
Order By: Relevance
“…The down-regulation of genes involved in chromatin assembly and ion homeostasis (cluster III, Fig. S3C) is consistent with the dedifferentiation of injury-activated Müller glia described previously (14,17,18,22,23).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The down-regulation of genes involved in chromatin assembly and ion homeostasis (cluster III, Fig. S3C) is consistent with the dedifferentiation of injury-activated Müller glia described previously (14,17,18,22,23).…”
Section: Resultssupporting
confidence: 88%
“…Our study differs from 3 previously published microarray-based gene expression profile studies of retinal regeneration in adult zebrafish (13-15) in 2 fundamental ways: (i) we used brief exposures to ultra-intense light to induce widespread and rapid photoreceptor death, whereas the earlier studies exposed fish to continuous light at lower intensities for several days (14,15) or surgically removed a small piece of retina (13), and (ii) we isolated the injury-activated Müller glia for RNA extraction and gene profiling analysis, whereas the other studies harvested RNA from the entire retina (13,14) or from laser-captured ONL tissue (15). Retinal injury induces a series of complex cellular responses in many cell types, including neurodegeneration and apoptosis of the damaged cells, stress responses in other retinal cells, and activation of microglia/macrophages (6,14,18).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Recent studies identified Müller glia as stem cells responsible for both persistent rod genesis (see above) and neuronal regeneration (Bernardos et al,, 2007, Yurco and Cameron, 2005, Kassen et al, 2007, Fausett and Goldman, 2006Fimbel et al, 2007;Thummel et al, 2008). Following the death of extant neurons, Müller glia de-differentiate, reenter the cell cycle and give rise to multipotent progenitors, which continue to proliferate, migrate and differentiate to replace the missing neurons.…”
Section: Introductionmentioning
confidence: 99%